Tone in REIT financial statements and institutional investments. Issue 3 (3rd July 2019) - Carstens, Riëtte; Freybote, Julia
ABSTRACT: We investigate the response of institutional REIT investors to the abnormally (net) positive tone in REIT financial statements. For non-REIT firms, sophisticated investors have been found to respond negatively to an abnormally positive tone due to managerial incentives to take advantage of information asymmetries and use a positive tone to manipulate investor perception. However, institutional REIT investors have an informational advantage as they either directly invest in commercial real estate as part of their portfolio management strategy or, at a minimum, have access to commercial real estate market data. Thus, they are able to evaluate the abnormally positive tone in REIT financial statements against their perception of conditions in the commercial real estate and derivative REIT market. For a sample of US REITs over the period of 2001 to 2017, we find that the response of institutional investors to the abnormally positive tone in REIT financial statements is time-varying and non-linear, irrespective of whether we use variables in levels or changes. In particular, in periods of institutional REIT investor optimism (pessimism), institutional REIT investors respond positively (negatively) to an abnormally positive tone and behave as net buyers (net sellers).